First case of trans apical implantation of an aortic valve in a patient with dextrocardia - vH Weich Hellmuth S (Journal of Cardiothoracic Surgery, 2012)
Abstract We describe the clinical presentation and implantation procedure of the first transcatheter aortic valve implantation described in a patient with dextrocardia.